Isolation and identification of iron ore-solubilising fungus - Rasheed Adeleke; Eugene Cloete; Damase Khasa (South African Journal of Science)
Potential mineral-solubilising fungi were successfully isolated from the surfaces of iron ore minerals. Four isolates were obtained and identified by molecular and phylogenetic methods as close relatives of three different genera, namely Penicillium (for isolate FO), Alternaria (for isolates SFC2 and KFC1) and Epicoccum (for isolate SFC2B). The use of tricalcium phosphate (Ca3(PO4)2)in phosphate-solubilising experiments confirmed isolate FO as the only phosphate solubiliser among the isolated fungi. The bioleaching capabilities of both the fungus and its spent liquid medium were tested and compared using two types of iron ore materials, conglomerate and shale, from the Sishen Iron Ore Mine as sources of potassium (K) and phosphorus (P). The spent liquid medium removed more K (a maximum of 32.94% removal, from conglomerate), than the fungus (a maximum of 21.36% removal, from shale). However, the fungus removed more P (a maximum of 58.33% removal, from conglomerate) than the spent liquid medium (a maximum of 29.25% removal, from conglomerate). The results also indicated a potential relationship between the removal of K or P and the production of organic acids by the fungus. A high production of gluconic acid could be related to the ability of the fungus to reduce K and P. Acetic, citric and maleic acids were also produced by the fungus, but in lower quantities. In addition, particle size and iron ore type were also shown to have significant effects on the removal of potassium and phosphorus from the iron ore minerals. We therefore conclude that the spent liquid medium from the fungal isolate FO can potentially be used for biobeneficiation of iron ore minerals.